Effect of Organizational Justice on Employees Engagement in Five Star Hotels in Luxor - Abd El-Salam, Muhammad Abd El-Monem Ebraheem; Abdelmawgoud, Mohamed T. A. (جامعة المنيا - كلية السياحة والفنادق, 2023)
The aim of this research is to examine the effect of organizational justice on employee engagement in five-star hotels in Luxor. The research utilized two measurement instruments to measure organizational justice and employee engagement. About 284 out of 292 forms distributed, were successfully filled out and collected. This research revealed that a positive correlation in five-star hotels between organizational justice dimensions and employees engagement. In addition, it also revealed that employees engagement can be predicted in the light of two dimensions of organizational justice; the first dimension was procedural justice followed by the interactional justice. Moreover, this research is the first empirical study in hospitality industry in Egypt that focused on examining the effect of organizational justice level on employees engagement in hotels. Finally, this research recommended that managers should increase organizational justice and make equitable to distribute incentives among staff and the promotion process to higher positions should be done on a fair basis.
Keywords: الثقافة التنظيمية -- الأداء الوظيفي -- نظام الحوافز -- الفنادق السياحية -- المناطق السياحية